İstanbul İlindeki Özel Hastanelerde Çalışan Hemşirelerin İş Tatminleri - (:unkn) unknown (My University, 2016)
GİRİŞ: İş tatmini kavramı pek çok bireysel ve örgütsel sonuca neden olduğu için tüm örgütlerde üzerinde önemle durulması gereken bir konudur. Personelin küçük bir bölümünün bile iş tatminsizliği yaşaması, yapılan işlerde olumsuz sonuçlara neden olabilmektedir. YÖNTEM: Tanımlayıcı tipteki bu çalışmada, özel hastanelerde çalışan hemşirelerin duydukları iş tatmini algıları belirlenerek, sosyodemografik özellikler ile arasındaki ilişkinin ortaya konulması amaçlanmıştır. Araştırma kapsamına, İstanbul'da bulunan JCI (Joint Commission International) Kalite Belgesi alan hastaneler alınırken, örneklemi çalışmayı kabul eden kurumlarda çalışan 662 hemşire oluşturmuştur. Veriler "Minesota İş Tatmini Ölçeği" uygulanarak toplanmıştır. SONUÇ: Çalışma sonucunda hemşirelerin, ortanın üstünde iş tatminine (3,45±0.591) sahip oldukları görülmüştür. Ayrıca, çalışanların iş tatminlerinin sosyodemografik özelliklerine göre farklılık gösterdiği (P<0,05) belirlenmiştir.

INTRODUCTION: Job satisfaction is a subject that needs to be place too much stress on because of its individual and organizational results in all organizations. Negative effects of job dissatisfaction can be experienced in the organization even if a few workers are not satisfied with their job.METHODS: Main aim in this article which was planned as a descriptive study was to reveal the relationship between socio-demographic characteristics and job satisfaction perceptions of the nurses working in private hospitals. The hospitals in Istanbul which possessed JCI (Joint Commission International) Quality Certificates were included in the study and 662 nurses working in institutions which agreed to participate in the study constituted the sampling size. Data were gathered using Minnesota Job Satisfaction Scale.RESULTS: As a result of the study, it was determined that the job satisfaction level of nurses was above the moderate level (X=3.45±0.591). Also, statistically significant differences have been found between job satisfaction levels according to socio-demographic characteristics of workers.
Job Satisfaction Of Nurses Working in Private Hospitals in Istanbul
Keywords: Hemşirelik